Analysis of Design Needs for Mobile Application Development Poetry Creation as a Learning Media for Writing Poetry - Kartini, Ari; Sunendar, Dadang; Sumiyadi; Yulianeta, Y (Universitas Muhammadiyah Malang, 2023)
21st-century education requires learning to be carried out by utilizing technology. To fulfill the demands of the 21st century, teachers should be directed and encouraged to integrate the use of technology-based media into the process of teaching and learning. The present study aims to investigate the needs that inform the development of an application as a learning medium for writing poetry at the high school level. To achieve the objective, the study utilized a qualitative approach involving the stages of data reduction, data presentation, and data interpretation. The data were collected through a questionnaire and interview and analyzed using basic descriptive statistics and qualitative analysis. The results showed that 1) students and teachers expect that the teaching and learning of poetry will utilize technology-based media such as Android-based cell phones. 2) In the Mobile Cipta Poetry application media, the students confirm the helpful features offered by the application, such as diction selection, relaxation music, sharing works, poetry manuscript banks, and peer evaluations. These findings indicate that the design of the Mobile Cipta Poetry (MCP) application has met the students’ and teachers’ needs. The study concludes that the difficulty and lack of motivation that the students face during the poetry writing activity may occur due to the lack of technology-based media. Therefore, it is necessary to develop IT-based media that can support the poetry writing process in the classroom.